The role of social support in predicting psychological well-being among private special needs school (SLB) teachers in Padang - Karina Amelia Putri; Dewi Fitriana; Rena Kinnara Arlotas (Psychological Research and Intervention, 2026)
The existence of good social support was found to help special needs teachers cope with the demands of their work, thereby improving their psychological well-being. This study aimed to examine the influence of social support on the psychological well-being of private special needs teachers in Padang. This study employed a quantitative approach, with 246 teachers in the population and 153 in the sample. The sampling technique used was purposive sampling. Data on social support were collected using the Social Provision Scale (SPS), and data on psychological well- being were collected using the Psychological Well-Being Scale (PWBS). This study used a simple regression analysis technique. The results indicated that social support had a significant impact on the psychological well-being of private SLB teachers in Padang city, with a regression coefficient of 0.528, p-value < 0.00, and R-squared value of 27.9%. This meant that the higher the level of social support a person had, the higher their level of psychological well-being.